The Upward Pricing Pressure Test for Merger Analysis: An Empirical Examination - Lydia Cheung (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2013)
The Upward Pricing Pressure (UPP) test developed by antitrust economists Joseph Farrell and Carl Shapiro marks a new era in antitrust and provides an alternative to the traditional concentration-based tests in merger analysis. In addition to being free of market de nition, the UPP's appeal lies in its ease of use: one simple formula indicates whether a merging rm has an incentive to increase prices postmerger. This paper rst establishes the theoretical relationship between the UPP and the standard structural merger simulation, namely, that the UPP is a merger simulation" that ignores the re-equilibration of all other endogenous variables except that product's own price. To assess the consequence of this simpli cation, I compute rue" UPP values for a cross-section of airline markets using structurally estimated price elasticities, and confront them with the standard" of a merger simulation. I examine the predictive accuracy of both the sign and magnitude of the UPP. I nd that it gives wrong sign predictions to an average 10% of the observations, and its value has an average correlation of 0:92 with the structurally simulated price changes. However, since this test is meant to bypass a complicated demand estimation, I then use the example of a simple logit demand to illustrate the consequence of using inaccurate demand-side inputs in the UPP: the test will give a wrong sign prediction over a much larger range of cost synergies. Lastly, I discuss the pass-through conditions for Farrell and Shapiro's proposition, demonstrate empirically that they are not innocuous, and show that their violation can lead to false positive results (type I errors) in the UPP.
Keywords: 330; merger; upward pricing pressure